Identification of two bone morphogenetic protein type I receptors in Drosophila and evidence that Brk25D is a decapentaplegic receptor. - Penton, A.; Chen, Y.; Staehling-Hampton, K.; Wrana, J.L.; Attisano, L.; Szidonya, J.; Cassill, J.A.; Massague, J.; Hoffmann, F.M. (Cell, 1994)
Drosophila sequences at chromosomal positions 25D (Brk25D) and 43E (Brk43E) are similar to the TGF beta type I receptor serine/threonine kinases and are expressed broadly during embryogenesis. Brk25D binds dpp protein and bone morphogenetic protein 2 with high affinity. Mutations affecting Brk25D map to the gene thick veins and block the expression of two decapentaplegic-responsive (dpp-responsive) genes, dpp and labial, in the embryonic midgut. Defects in Brk25D receptor function combined with reduced expression of dpp ligand produce mutant phenotypes in the embryo and adult. Brk43E is the product of the gene saxophone, which also interacts with dpp. We conclude that dpp signaling in vivo is mediated by at least two receptors, Brk25D and Brk43E.